身份认同的争议 ：归化运动员与新加坡的案例研究 = Controversy of identity : a case study of naturalized athletes and Singapore - 邱志威 Koo, Zhi Wei (2016)
One particular segment of Chinese immigrants that this paper is concerned about is the Naturalized Athletes. Since the inception of the Foreign Talent Sports Scheme was introduced in 1993 as a means to attract high-quality foreign-born athletes to represent Singapore in regional and global sporting competitions, there have been 64 cases of foreign-born athletes who are naturalized and are granted Singapore Citizenship. However, there have been criticisms of the Scheme too, with the main criticism being that Naturalized Athletes leaving Singapore after retirement without contributing back to the society. This dissertation seeks to explain the research motives and audience, aims to highlight naturalized athletes’ characteristics and the controversy surrounding them and finally explains the athletes’ lack of belonging based on research findings.